2020
DOI: 10.1055/s-0040-1708002
|View full text |Cite
|
Sign up to set email alerts
|

Acetic Acid Promoted Direct Iodination of Terminal Alkynes with N-Iodosuccinimide: Efficient Preparation of 1-Iodoalkynes

Abstract: An efficient and highly chemoselective approach for the direct iodination of terminal alkynes using acetic acid as N-iodosuccinimide activated reagent under metal-free conditions has been developed. This facile process tolerates a variety of terminal alkynes and provides the desired products in good to excellent yields (up to 99%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
(2 reference statements)
1
4
0
Order By: Relevance
“…This reaction is reported in the literature by Liu et al , 56 which explains the high conversion with corresponding low yield. The fact that uncatalyzed NIS reactions showed a low yield and conversion corresponds to the observation by Yao et al , 54 where they showed that the chemoselectivity and regioselectivity are driven by the presence of an acid catalyst. The absence of the catalyst can lead to the formation of a diiodovinyl substrate instead of the desired product.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…This reaction is reported in the literature by Liu et al , 56 which explains the high conversion with corresponding low yield. The fact that uncatalyzed NIS reactions showed a low yield and conversion corresponds to the observation by Yao et al , 54 where they showed that the chemoselectivity and regioselectivity are driven by the presence of an acid catalyst. The absence of the catalyst can lead to the formation of a diiodovinyl substrate instead of the desired product.…”
Section: Resultssupporting
confidence: 76%
“…1 ). In this study, we focused on two different routes simultaneously to determine the most effective reaction conditions: (i) the first route utilizes N -iodosuccinimide (NIS) as the iodinating agent, 54 while (ii) the second route involves chloramine-B as the oxidant and iodine salts as the halogen source. 55 …”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of iodoalkynyl substrates was carried out under conventional procedures involving iodination of terminal alkyne with iodinating reagents, such as potassium iodide, hypervalent iodonium salts or Niodosuccinimide (NIS) to access corresponding 1iodoacetylenes. [31][32][33] The latter approach was proved to be efficient in our previous work. [30] Next, syntheses of 1,3-diynes were carried out using a Cadiot-Chodkiewicz coupling between a variety of iodoalkyne DNA-conjugates and terminal alkynes (Table 1).…”
Section: Introductionmentioning
confidence: 96%
“…We initiated the study by widening the scope of substrates available for thiophene formation. The synthesis of iodoalkynyl substrates was carried out under conventional procedures involving iodination of terminal alkyne with iodinating reagents, such as potassium iodide, hypervalent iodonium salts or N ‐iodosuccinimide (NIS) to access corresponding 1‐iodoacetylenes [31–33] . The latter approach was proved to be efficient in our previous work [30] …”
Section: Introductionmentioning
confidence: 99%
“…Hypervalent iodine sources have also been used, as have oxidants, as co- ISSN 2053ISSN -2296 reactants (Liu et al 2017). Amongst the milder methods reported, several have focused on the application of N-iodosuccinimide in acetic acid (Yao et al, 2020a), with -alumina (Yao et al, 2020b), and in acetone with silver nitrate as catalyst (Hofmeister et al, 1984). Herein we report the unexpected isolation and characterization of the unreacted 1:1 cocrystals formed on rapid evaporation of mixtures of the diethynylpyridines 2,6-diethynylpyridine (26DEP) and 3,5-diethynylpyridine (35DEP), and the N-halosuccinimides N-bromosuccinimide (NBS) and N-iodosuccinimide (NIS) in acetone (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%